The 80s - photographing Britain - Akkouche, Bilal; Batchen, Geoffrey 1956-; Bishton, Derek; Dahmani, Taous R. 1990-; Sealy, Mark 1960-; Stacey, Noni (Tate Publishing, 2024)
Explore one of the UK's most critical decades, the 1980s. This exhibition traces the work of a diverse community of photographers, collectives and publications -creating radical responses to the turbulent Thatcher years. Set against the backdrop of race uprisings, the miner strikes, section 28, the AIDS pandemic and gentrification - be inspired by stories of protest and change. At the time, photography was used as a tool for social change, political activism, and artistic and photographic experiments. See powerful images that gave voice and visibility to underrepresented groups in society. This includes work depicting the Black arts movement, queer experience, South Asian diaspora and the representation of women in photography. This exhibition examines how photography collectives and publications highlighted these often-unseen stories, featured in innovative photography journals such as Ten 8 and Cameraworks. It will also look at the development of Autograph ABP, Half Moon Photography Workshop, and Hackney Flashers. Visitors will go behind the lens to trace the remarkable transformation of photography in Britain and its impact on art and the world. -- Tate website
Impressum: First published ... on the occasion of the exhibition "The 80s - Photographing Britain", Tate Britain, London, 21 November 2024 - 5 May 2025
Keywords: Geschichte 1980-1990; Fotografie; Großbritannien; Photography, Artistic / 20th century / Exhibitions; Nineteen eighties / Exhibitions; Nineteen eighties / Pictorial works; Great Britain / History / 20th century / Exhibitions; Great Britain / History / 20th century / Pictorial works; Ausstellungskatalog -- Tate Britain -- 21.11.2024-05.05.2025 -- London; Bildband